Direct imaging of white matter ultrashort T2∗ components at 7 Tesla - Müller, Max; Egger, Nico; Sommer, Stefan; Wilferth, Tobias; Meixner, Christian; Laun, Frederik Bernd; Mennecke, Angelika; Schmidt, Manuel; Huhn, Konstantin; Rothhammer, Veit; Uder, Michael; Dörfler, Arnd; et al. (Magnetic Resonance Imaging, 2022)
Purpose: To demonstrate direct imaging of the white matter ultrashort T2∗ components at 7 Tesla using inversion recovery (IR)-enhanced ultrashort echo time (UTE) MRI. To investigate its characteristics, potentials and limitations, and to establish a clinical protocol. Material and methods: The IR UTE technique suppresses long T2∗ signals within white matter by using adiabatic inversion in combination with dual-echo difference imaging. Artifacts arising at 7 T from long T2∗ scalp fat components were reduced by frequency shifting the IR pulse such that those frequencies were inverted likewise. For 8 healthy volunteers, the T2∗ relaxation times of white matter were then quantified. In 20 healthy volunteers, the UTE difference and fraction contrast were evaluated. Finally, in 6 patients with multiple sclerosis (MS), the performance of the technique was assessed. Results: A frequency shift of −1.2 ppm of the IR pulse (i.e. towards the fat frequency) provided a good suppression of artifacts. With this, an ultrashort compartment of (68 ± 6) % with a T2∗ time of (147 ± 58) μs was quantified with a chemical shift of (−3.6 ± 0.5) ppm from water. Within healthy volunteers' white matter, a stable ultrashort T2∗ fraction contrast was calculated. For the MS patients, a significant fraction reduction in the identified lesions as well as in the normal-appearing white matter was observed. Conclusions: The quantification results indicate that the observed ultrashort components arise primarily from myelin tissue. Direct IR UTE imaging of the white matter ultrashort T2∗ components is thus feasible at 7 T with high quantitative inter-subject repeatability and good detection of signal loss in MS.
Created from Fastlane, Scopus look-up
Keywords: 7 Tesla; Multiple sclerosis; Myelin; Relaxometry; Ultrashort echo time (UTE); White matter